2018
DOI: 10.1080/2162402x.2018.1474319
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil and bevacizumab plus anakinra for patients with metastatic colorectal cancer refractory to standard therapies (IRAFU): a single-arm phase 2 study

Abstract: In preclinical models, IL-1β inhibition could enhance the efficacy of fluorouracil (5-FU). In this phase 2 study, we assessed the activity and safety of 5-FU plus bevacizumab and anakinra (an IL-1β and α inhibitor) in patients with metastatic colorectal (mCRC) refractory to chemotherapy and anti-angiogenic therapy.Eligible patients had unresectable mCRC; were refractory or intolerant to fluoropyrimidine, irinotecan, oxaliplatin, anti-VEGF therapy, and anti-EGFR therapy (for tumors with wild-type KRAS). Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…A 10-year trial of daily Anakinra with weekly low dose dexamethasone in 47 patients with smoldering myeloma resulted in significantly increased survival (Lust et al, 2009;Lust et al, 2016). Improved survival has been reported when Anakinra is added to the standard of therapy with fluorouracil in advanced metastatic colorectal cancer (Isambert et al, 2018), hormone negative breast cancer , and in advanced pancreatic cancer (Becerra et al, 2018;Whiteley et al, 2016). In pre-clinical studies, Anakinra also abated chimeric antigen receptor (CAR)-T-cell-induced cytokine release syndrome and neurotoxicity (Giavridis et al, 2018;Norelli et al, 2018).…”
Section: Il-1 Family Members In Cancer Progressionmentioning
confidence: 99%
“…A 10-year trial of daily Anakinra with weekly low dose dexamethasone in 47 patients with smoldering myeloma resulted in significantly increased survival (Lust et al, 2009;Lust et al, 2016). Improved survival has been reported when Anakinra is added to the standard of therapy with fluorouracil in advanced metastatic colorectal cancer (Isambert et al, 2018), hormone negative breast cancer , and in advanced pancreatic cancer (Becerra et al, 2018;Whiteley et al, 2016). In pre-clinical studies, Anakinra also abated chimeric antigen receptor (CAR)-T-cell-induced cytokine release syndrome and neurotoxicity (Giavridis et al, 2018;Norelli et al, 2018).…”
Section: Il-1 Family Members In Cancer Progressionmentioning
confidence: 99%
“…Anakinra, which neutralizes both IL‐1 ligands, has been reported to inhibit colon tumour growth in preclinical studies and has been investigated as a therapy across various malignancies. In metastatic colorectal cancer patients, anakinra administration was reported to provide significant survival benefit and improved quality of life scores, when added to standard‐of‐care chemotherapy for colorectal cancer . However, in such settings the relative short half‐life of anakinra and requirement for continuous administration is problematic and can hinder patient adherence, prompting investigation of anti‐IL‐1 neutralising antibodies .…”
Section: Common Inflammatory Diseases Responsive To Anti Il‐1 Therapiesmentioning
confidence: 99%
“…The combination of anakinra plus chemotherapy was not associated with any adverse events such as serious infection. Similar to the trial of anti-IL1α in patients with metastatic colorectal cancer (9), some patients with breast cancer reported reduced pain and increased quality of life on anakinra plus chemotherapy and in other studies, anakinra reduced the “sickness syndromes” of chemotherapy used to treat metastatic colorectal cancer but also increased overall survival (3). Three of the 11 patients in the Palucka trial are still alive (1).…”
mentioning
confidence: 88%
“…Anakinra is increasingly used as adjunct therapy to reduce the inflammation of metastatic cancer. A trial in metastatic colorectal cancer showed significant survival benefit when anakinra was added to standard-of-care chemotherapy for colorectal cancer (3) and patients with pancreatic cancer also benefit when anakinra is added to chemotherapy (4). Moreover, in these trials, the patients report improved quality-of-life scores with the use of anakinra.…”
mentioning
confidence: 99%
See 1 more Smart Citation